Cultural interventions to treat addictions in Indigenous populations: findings from a scoping study - Rowan, Margo; Poole, Nancy; Shea, Beverley; Gone, Joseph P; Mykota, David; Farag, Marwa; Hopkins, Carol; Hall, Laura; Mushquash, Christopher; Dell, Colleen (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Cultural interventions offer the hope and promise of healing from addictions for Indigenous people.a However, there are few published studies specifically examining the type and impact of these interventions. Positioned within the Honouring Our Strengths: Culture as Intervention project, a scoping study was conducted to describe what is known about the characteristics of culture-based programs and to examine the outcomes collected and effects of these interventions on wellness. Methods This review followed established methods for scoping studies, including a final stage of consultation with stakeholders. The data search and extraction were also guided by the “PICO” (Patient/population, Intervention, Comparison, and Outcome) method, for which we defined each element, but did not require direct comparisons between treatment and control groups. Twelve databases from the scientific literature and 13 databases from the grey literature were searched up to October 26, 2012. Results The search strategy yielded 4,518 articles. Nineteen studies were included from the United States (58%) and Canada (42%), that involved residential programs (58%), and all (100%) integrated Western and culture-based treatment services. Seventeen types of cultural interventions were found, with sweat lodge ceremonies the most commonly (68%) enacted. Study samples ranged from 11 to 2,685 clients. Just over half of studies involved quasi-experimental designs (53%). Most articles (90%) measured physical wellness, with fewer (37%) examining spiritual health. Results show benefits in all areas of wellness, particularly by reducing or eliminating substance use problems in 74% of studies. Conclusions Evidence from this scoping study suggests that the culture-based interventions used in addictions treatment for Indigenous people are beneficial to help improve client functioning in all areas of wellness. There is a need for well-designed studies to address the question of best relational or contextual fit of cultural practices given a particular place, time, and population group. Addiction researchers and treatment providers are encouraged to work together to make further inroads into expanding the study of culture-based interventions from multiple perspectives and locations.